Dominasi Medis Modern Atas Medis Tradisional Suku Sumuri, Teluk Bintuni, Papua Barat - Atik Triratnawati (Faculty of Social and Political Science, Universitas Airlangga, 2017)
Declaration 1990-2015 MDG's 4 and 5 points in Indonesia fail due to a decrease in maternal and infant mortality rate is not reached until three quarters. Sumuri District, in West Papua is one of the area that maternal and infant mortality rates high, althought free health care for its residents. This paper wants to explore how the interaction between modern medicine and local medicine so the dominant health care in the community will be identified. Ethnographic study by living together with the local community to make the observation of the patient's health centers, community leader interviews, adult population, health workers and mini Focus Group Discussion among 4 mothers who has under 5 years old children conducted in June 2014. Government, oil and gas companies are aggressively introducing modern medical to the residents of SumuriDistrict, as a result communities have high interest to visit the health center for treatment and natural healing tends to disappear. New health institutions such as health centers, integrated health, midwives, nurses, physicians are able to shift the role of traditional birth attendants, traditional healer or traditional medicine. As a result of social relations within the extended family was replaced by a stronger role of midwives, nurses and doctors. However, the older generation tends to be more suitable with traditional healing compare to modern medicine.